Minutes of the 44th Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of Minutes of the 43rd Meeting of the Academic Council. 2. Review of the progress and implementation of decisions of the 43rd Meeting of the Academic Council. 3. Update on 7th Convocation. 4. Proposal for Bachelor in Social Science (BSS) in Anthropology. 5. Proposal for Certificate Course on Construction Management. 6. Proposal for Certificate Course in TESOL. 7. Proposal for Pre-University Mathematics Course. 8. Proposal for Revisions in Credit Distribution of MDMP courses and Approval of MDMP Academic Calendar. 9. Proposal for Centre for Urban Equity and Health (CUEH). 10. Proposal for Centre on Gender and Social Transformation (CGST) at the BRAC Development Institute (BDI). 11. Setting up of a Review Committee for Research Proposal. 12. Miscellaneous: 12.1. Allowing additional time to complete MDS Program. 12.2. Application for continuation of studies. 12.3. Continuation of Studies beyond 3rd times probation. 12.4. Application seeking withdrawal of expulsion order and continuation of study in BRAC University. 12.5. Application for Readmission.